Description Of Waste Management System In Soe City, South Timor Regency - Deskrianti Tanaem (Eduvest - Journal of Universal Studies, 2021)
Waste management is a systematic, comprehensive, sustainable activity that includes waste reduction and handling. The existence of waste can have a health effect on the environment and society if it is not handled seriously. The influence of waste on the environment that can damage the aesthetics of the environment and for health can indirectly be in the form of vector-borne diseases that breed in the waste. This study was conducted to determine the description of the waste management system in Soe City. The research method used is a descriptive survey where the research is carried out with the main aim of making a picture or description of a situation objectively. The number of samples in this study were 26 TPS and 1 TPA and the managers of each TPS and TPA. The analysis used is univariate analysis. Based on the results of the study, it showed that of the total 26 TPS in Soe City, 3 (11.5%) were in the good category, while 23 (88.5%) were in the bad category. The waste management system that starts from waste sorting is 26 (100.0%) TPS is bad in sorting waste, bad waste collection is 17 (65.4%) while good is 9 TPS (34.6%). The process of transporting waste from TPS to TPA is still bad at 17 (65.4%) TPS and 9 (34.6%) TPS have good category, for waste processing from 26 TPS no one does waste processing, and final waste processing Soe City TPA is still bad at destroying waste. The Soe City Government is expected to pay attention to waste management issues as well as support and facilitate the solid waste management system in Soe City, in order to reduce the negative impact on environmental health and public health